(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
ESP (English for Specific Purposes) is special English classes for students who are studying in other spheres. As English is an international language, it turned into a means of globalization. Therefore, English is being taught as a main subject in all education centers. However, teaching ESP is not easy job, it differs from teaching General English. It requires professional teachers, special syllabus, books and others. The most important thing in teaching ESP is identifying students` needs and organizing the lesson based on the students` needs. Choosing appropriate methods and approaches is also essential. It is beneficial to integrate various technological devices during the lesson as it helps the students to learn better. Taxation is one of the spheres in which the students are learning English language as one of their main subjects.